Stereoselective Synthesis of C-Aryl-α-Glycosides by Reductive C(sp2)–C(sp3) Cross-Coupling Reaction - Kudo, Noyuri; Chiba, Suzuka; Ono, Shunsuke; Nagatoishi, Masataka; Yoritate, Makoto; Karasawa, Satoru; Usui, Kazuteru; Hirai, Go (Synlett, 2024)
C-Aryl glycosides have attracted considerable interest as biologically active natural products and as O-aryl glycoside mimetics in drug discovery. Here, we describe a straightforward synthesis of C-aryl glycosides by photoredox/Ni dual-catalyzed reductive cross-coupling between glycosyl bromides and aryl bromides. This methodology enables a highly α-stereoselective synthesis of C-aryl glucosides, galactosides, and mannosides.
Keywords: glycosides; photoredox catalysis; nickel catalysis; cross-coupling; stereoselectivity; conformational restriction